2007
DOI: 10.1590/s0066-782x2007001600006
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida de pacientes hipertensos em tratamento ambulatorial

Abstract: When the SF-36 was administered no changes in QOL were detected between the groups because it is an asymptomatic chronic disease. The SF-36 did not properly assess emotional aspects in our case series of hypertensive patients that had high behavior variability. Group A showed lower quality sex life; however, this was not related to the number and type of medication used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
18

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 16 publications
1
23
0
18
Order By: Relevance
“…In the study by Silqueira 7 , the average value found was 77.8; in the one by Gusmão and Pierin 22 , the average was 73.0; and in the one by Cavalcante 5 , the score was 72.0. In the study by Brito et al 25 , the GH had the lowest score, 53.5.…”
Section: General Health (Gh)mentioning
confidence: 87%
See 1 more Smart Citation
“…In the study by Silqueira 7 , the average value found was 77.8; in the one by Gusmão and Pierin 22 , the average was 73.0; and in the one by Cavalcante 5 , the score was 72.0. In the study by Brito et al 25 , the GH had the lowest score, 53.5.…”
Section: General Health (Gh)mentioning
confidence: 87%
“…The SF-36 (The Medical Outcomes Study 36-Item ShortForm Health Survey) [5][6][7] is a tool widely used to reflect the QOL of patients in a wide variety of populations, including aspects such as function, dysfunction and emotional and physical well-being. Specific instruments assess health concepts specific to a disease or an intervention.…”
mentioning
confidence: 99%
“…The group which performed regular physical exercise presented better HRQOL score both in the emotional and physical domains, as well as used less medication than the sedentary group. A possible explanation for these results may be in the kind of treatment, considering that in the treatment of the physically active group there was involvement of a multidisciplinary team, which made it possible that educational and information aspects contributed to better understanding of the hypertensive disease, besides the positive influence provided by the social interaction present in this kind of activity 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study in which QOL was assessed through the SF-36 questionnaire, hypertensive patients helped at the first-aid office presented the perception of physical aspects with worse scores than the emotional ones 10 . Another investigation using the same generic instrument demonstrated that the QOL of 131 hypertensive subjects presented physical and emotional compromising 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation